Angiotensin‐converting enzyme 2 and transmembrane protease serine 2 in female and male patients with end‐stage kidney disease. (9th April 2022) - Arefin, Samsul; Hernandez, Leah; Ward, Liam J.; Schwarz, Angelina; ,; Barany, Peter; Stenvinkel, Peter; Kublickiene, Karolina
Abstract: Background: Individuals with chronic kidney disease are affected by acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) due to multiple comorbidities and altered immune system. The first step of the infection process is the binding of SARS‐CoV‐2 with angiotensin‐converting enzyme 2 (ACE2) receptor, followed by its priming by transmembrane protease serine 2 (TMPRSS2). We hypothesized that circulating soluble ACE2 levels, as well as the expressions of ACE2 and TMPRSS2 in the microvasculature, are increased in patients with end‐stage kidney disease (ESKD). Methods: A total of 210 participants were enrolled, representing 80 ESKD patients and 73 non‐CKD controls for soluble ACE2, and 31 ESKD and 26 non‐CKD controls for vasculature and fat tissue bioassays. We have assessed ACE2 expression in blood using ELISA and in tissue using immunofluorescence. Results: Soluble ACE2 levels were higher in ESKD patients compared to controls; however, there is no sex difference observed. In ESKD and controls, soluble ACE2 positively correlated with Interleukin 6 (IL‐6) and C‐reactive protein (CRP), respectively. Similarly, ACE2 tissue expression in the vasculature was higher in ESKD patients; moreover, this higher ACE2 expression was observed only in male ESKD patients. In addition, TMPRSS2 expression was observed in vessels from males and females but showed no sex difference. The expression of ACE2 receptor was higher in ESKD patients on ACE‐inhibitor/angiotensin blocker treatment. Conclusion: ESKD is associated with increased ACE2 levels in the circulation and pronounced in male vasculature; however, further studies are warranted to assess possible sex differences on specific treatment regime(s) for different comorbidities present in ESKD.